Islamic Boarding School and the Deradicalization Efforts of Islamic Education in Madura - Saleh, M Nurul Ikhsan; Nudin, Burhan; Khusaini, Khusaini; Alim, Puji; Putri, Ida Ayu (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2019)
Deradicalization has become a priority agenda of Islamic education studies in the last few decades. This study aims to comprehensively understand the efforts to deradicalize Islamic Education conducted by the Annuqayah Islamic boarding school in Madura, East Java, Indonesia. Researchers used qualitative methods with a case study. Data collection was done through in-depth interviews, documentation studies, and observations. The results of this study found ten efforts at deradicalization conducted by Annuqayah Islamic boarding school, i.e. (1) Reactualization of learning resources; (2) Strengthening anti-radicalism; (3) Increasing literacy and discussion skills; (4) Strengthening the spirits of nationalism; (5) Promoting the principle of wasathiyah (moderatism); (6) Applying the theological concept of Ahlus-Sunnah wal Jama’ah (the group who perform the sunnah); (7) Initiating anti-radicalism curriculum; (8) Implementing progressive manhaj; (9) Formulating halaqa (meetings) with ulama; and (10) Empowering friendship and brotherhood. The implications of this research provided considerations in evaluating the curriculum, teaching materials, and teaching and learning process to support the creation of Islamic education institutions that promote peace, non-violence, and rahmatan lil alamin.